2007
DOI: 10.1007/s10327-006-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

Pythium and Phytophthora species associated with root and stem rots of kalanchoe

Abstract: Pythium and Phytophthora species were isolated from kalanchoe plants with root and stem rots. Phytophthora isolates were identifi ed as Phytophthora nicotianae on the basis of morphological characteristics and restriction fragment length polymorphism (RFLP) analysis of the rDNA-internal transcribed spacer regions. Similarly, the Pythium isolates were identifi ed as Pythium myriotylum and Pythium helicoides. In pathogenicity tests, isolates of the three species caused root and stem rots. Disease severity caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In the USA, it was found that P. helicoides was virulent in several crops such as bell pepper and caused root and stem rot of Begonia (Chellemi et al 2000;Yang et al 2013). In Japan, the species was identified to infect miniature r o s e , a n d t o c a u s e r o o t a n d s t e m r o t o f Chrysanthemum and Kalanchoe (Kageyama et al 2002;Tsukiboshi et al 2007;Watanabe et al 2007). The disease transmission test on miniature roses showed that the disease spread throughout the bench 10 days post-inoculation of the plants placed in the bench center (Kageyama et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…In the USA, it was found that P. helicoides was virulent in several crops such as bell pepper and caused root and stem rot of Begonia (Chellemi et al 2000;Yang et al 2013). In Japan, the species was identified to infect miniature r o s e , a n d t o c a u s e r o o t a n d s t e m r o t o f Chrysanthemum and Kalanchoe (Kageyama et al 2002;Tsukiboshi et al 2007;Watanabe et al 2007). The disease transmission test on miniature roses showed that the disease spread throughout the bench 10 days post-inoculation of the plants placed in the bench center (Kageyama et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Pythium root rot continually threatens the productivity of several types of crops including cucumbers, sweet peppers, tomatoes, lettuce, spinach, roses, and chrysanthemums (Sutton et al, 2006). The principal causal agent of rose root rot disease is P. helicoides (Kageyama et al, 2002;Watanabe et al, 2007). The root rot disease has also been observed in rockwool cultures of cutting rose and has spread in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The root rot disease of rose and kalanchoe caused by P. helicoides is most severe at temperatures higher than 35°C (Kageyama et al 2002;Watanabe et al 2007), and in fact the disease is prevalent in summer. However, zoospore formation in P. helicoides is induced at 25-30°C (Kageyama et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…(Kageyama et al 2002(Kageyama et al , 2003Watanabe et al 2007). The pathogen also affects cutting roses grown in rock wool culture, a hydroponic culture system in which the nutrient solution is recirculated.…”
Section: Introductionmentioning
confidence: 99%